2018
DOI: 10.1021/acs.jafc.8b01481
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Gut (Gallus gallus) Microbiota Following the Consumption of Zinc Biofortified Wheat (Triticum aestivum)-Based Diet

Abstract: The structure and function of cecal microbiota following the consumption of a zinc (Zn) biofortified wheat diet was evaluated in a well-studied animal model of human nutrition ( Gallus gallus) during a six-week efficacy trial. Using 16S rRNA gene sequencing, a significant increase in β- but not α-microbial diversity was observed in the animals receiving the Zn biofortified wheat diet, relative to the control. No significant taxonomic differences were found between the two groups. Linear discriminant analysis r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 66 publications
1
69
0
Order By: Relevance
“…Reed et al showed that broiler chickens that were fed a Zn-biofortified, wheat-based diet had increased microbial beta-diversity, with concomitant increases in beneficial short chain fatty acid-producing lactic acid bacteria--suggesting that this type of diet beneficially restructures the gut microbiota. 102 In line with our present study, 2 weeks of dietary supplementation with manganese was recently demonstrated to alleviate DSS-induced colitis in adult mice in the absence of changes in the gut microbiome. 107 It was recently reported that excess dietary Zn causes oxidative stress, enhances gut permeability, and modifies the microbiota in mouse pups.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Reed et al showed that broiler chickens that were fed a Zn-biofortified, wheat-based diet had increased microbial beta-diversity, with concomitant increases in beneficial short chain fatty acid-producing lactic acid bacteria--suggesting that this type of diet beneficially restructures the gut microbiota. 102 In line with our present study, 2 weeks of dietary supplementation with manganese was recently demonstrated to alleviate DSS-induced colitis in adult mice in the absence of changes in the gut microbiome. 107 It was recently reported that excess dietary Zn causes oxidative stress, enhances gut permeability, and modifies the microbiota in mouse pups.…”
supporting
confidence: 91%
“…99 Zinc's direct impact on the gut microbiota and subsequent host growth has been evaluated in several studies of young livestock animals (piglets, calves, and broiler chickens) that differed in their design (dose levels, measurement time points, etc) and methods. [100][101][102] Most studies have reported small, beneficial effects-suggesting that Zn may shape the intestinal microbiota. However, a consensus is currently lacking.…”
mentioning
confidence: 99%
“…The 7.5% teff group demonstrated a significantly lower LA:DGLA ratio, signifying a relative increase in Zn status, compared to both control groups ( p < 0.05). We have previously demonstrated the LA:DGLA ratio as a novel physiological biomarker of zinc status [ 19 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Given the nutritional advantages of teff, especially its high concentration of trace minerals, it is important to evaluate other intrinsic factors that influence absorption and bioavailability. Therefore, using the validated, well-established Gallus gallus in vivo model [ 6 , 12 , 13 , 14 , 15 , 19 , 20 ], we sought to assess the effects of the intra-amniotic administration of teff seed extracts on serum and tissue Fe and Zn status, as well as on multiple parameters that influence trace mineral absorption and bioavailability, i.e., intrinsic phytate and polyphenolic concentration, enterocyte gene expression of various trace mineral dependent proteins, and brush border membrane morphology. Additionally, 16S rRNA gene sequencing of cecal contents was utilized to analyze potential alterations in intestinal microbiota structure and function from teff extracts.…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA extraction from duodenal and heart tissue (30 mg) using Qiagen RNeasy Mini Kit (RNeasy Mini Kit, Qiagen Inc., Valencia, CA, USA), cDNA synthesis and real time-polymerase chain reaction (RT-PCR) analysis were performed as previously described 38,81 with minor adjustments. In brief, the cycle product (Cp) of each gene (2020) 10:2297 | https://doi.org/10.1038/s41598-020-57598-3 www.nature.com/scientificreports www.nature.com/scientificreports/ was quantified using a seven-point standard curve in duplicate.…”
Section: Gene Expression Analysis (Tissue Harvesting Rna Isolation mentioning
confidence: 99%